2002
DOI: 10.1007/s00264-002-0353-5
|View full text |Cite
|
Sign up to set email alerts
|

Bone substitutes as carriers for transforming growth factor-β1 (TGF-β1)

Abstract: We studied the suitability of three different hydroxyapatite materials (Endobone, Bio-Oss and Algipore) as carriers for the bone growth promoting factor TGF-beta(1). The hydroxyapatite materials either were incubated for 24 h or directly loaded with hrTGF-beta(1) (Diagnostic Products Corporation, DPC) at a concentration of 10 ng hrTGF-beta(1)/mg. For the release experiment the hydroxyapatite materials covered with hrTGF-beta(1) were either suspended in pure phosphate buffered saline (PBS) or human serum albumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
0
13
0
1
Order By: Relevance
“…However, the lack of signs of foreign body reaction to the bone mineral particles indicated indeed that the material was probably well tolerated by the host tissues. DBBM has been successfully used as a carrier for TGF-b1 (Gille et al 2002). In the present investigation, when EMD was used in combination with DBBM and GBR, no additional beneficial effects in terms of new bone formation could be demonstrated, indicating that enamel matrix proteins may not act as an additional stimulus for bone formation even when combined with an osteoconductive xenograft.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…However, the lack of signs of foreign body reaction to the bone mineral particles indicated indeed that the material was probably well tolerated by the host tissues. DBBM has been successfully used as a carrier for TGF-b1 (Gille et al 2002). In the present investigation, when EMD was used in combination with DBBM and GBR, no additional beneficial effects in terms of new bone formation could be demonstrated, indicating that enamel matrix proteins may not act as an additional stimulus for bone formation even when combined with an osteoconductive xenograft.…”
Section: Discussionmentioning
confidence: 55%
“…Hence, its use has been recommended in order to provide scaffold for the regeneration of various bone defects. DBBM has been successfully used as a carrier for TGF-b1 (Gille et al 2002). However, distant from the host bone, DBBM was usually embedded entirely into fibrous connective tissue.…”
Section: Discussionmentioning
confidence: 99%
“…This material is biocompatible, osteoconductive and has an additional desirable property of being slowly resorbable and replaced by newly formed bone (Ricci et al 1992, Schopper et al 2003, Ewers et al 2004). In in vitro studies, this material proved to be a suitable carrier for bone morphogenic proteins and growth factors (Herr et al 1993, Gille et al 2002), and its use in sinus augmentation demonstrated good clinical results (Ricci et al 1992, Schopper et al 2003). In the present study, the short‐ and long‐term effects of PRP on sinus augmentation using autogenous bone and Algipore ® were compared.…”
mentioning
confidence: 99%
“…Carriers fabricated from apatite materials that enable the controlled release of functional molecules are currently under investigation. Molecular release from apatite materials, initially incorporating the functional molecule, is achieved in vivo by desorption, depending on the local environment [87][88][89][90]. Therefore, an understanding of the adsorption and desorption kinetics of the functional molecules of HAp is crucial for achieving optimal drug release.…”
Section: Apatite Materials As Drug and Gene Deliv-ery Systemsmentioning
confidence: 99%